The shortage of cooking oil packet in University Apartment Phase 1, Sepanggar Kota Kinabalu Sabah / Innah Soliha Sahirin - Sahirin, Innah Soliha (2017)
It is the daily necessities of the people where cooking oil is needed. The importance of cooking oil to consumers in business, it has indeed been proven. This is because cooking oil is used to cook the tradable food. As an example, for business (food) and side dishes. The purpose of this study is to identify the constraints cooking oil among consumers in Sabah, which focuses on the study area namely in Sepanggar, Kota Kinabalu Sabah. In this study, the types consumers, consumer characteristics and the list of uses of cooking oil are reviewed based on demographic factors to see the significant impacts possible affect cooking oil constraints in the study area. Percentage is used in analyzing the data acquired. The findings reveal that the issue of packet cooking oil constraints in influenced by various factors. Studies have also been conducted on the types packaged cooking oil users who need it most. The findings of this study can help producers and factories packaged cooking oil in improving and increasing production at retail outlets, and the income of entrepreneurs and operators shop. In addition, it also helps to improve the socio-economic population local. Due to the purchase of cooking oil, especially packets are important among consumers especially merchants, hence it is expected to study this can contribute and can be applied in University Apartment Phase 1, Sepanggar Kota Kinabalu Sabah and other places.